Low-Density Lipoprotein Cholesterol Treatment Target Achievement in Patients with Myocardial Infarction, Percutaneous Coronary Intervention, or Stroke in Hong Kong - Joseph E Blais; Vincent KC Yan; Jiaxi Zhao; Celine SL Chui; Ian CK Wong; Chung Wah Siu; Esther W Chan (Reviews in Cardiovascular Medicine, 2022)
Background: Elevated concentrations of low-density lipoprotein cholesterol (LDL-C) are an important cause of recurrent cardiovascular events. This study aimed to describe the distribution and achieved concentrations of LDL-C among patients with myocardial infarction (MI), percutaneous coronary intervention (PCI), stroke, or transient ischaemic attack (TIA) in Hong Kong. Methods: Patients with a lipid test from a public hospital were identified from the Clinical Database and Analysis Reporting System of the Hong Kong Hospital Authority. Among patients with an inpatient hospitalization for MI, PCI, stroke or TIA, between 2003 to 2016, the distribution of LDL-C levels and the number (%) of patients achieving an absolute concentration of LDL-C <1.8 mmol/L at baseline (in-hospital) and during 12 months after hospital discharge were described. Results: A total of 18417 patients were included (mean [SD] age, 70.0 [12.9] years; male, 60.3%), of which 3637 had MI, 4096 had PCI, and 10684 had stroke or TIA. At hospital discharge 12082 (65.6%) patients were prescribed statins, 690 (3.7%) were prescribed nonstatins, and 1849 (10.0%) achieved an LDL-C <1.8 mmol/L. Overall, 5654 (30.7%) patients did not have LDL-C result available within 12 months of discharge (MI, 605 [16.6%]; PCI, 432 [10.5%]; stroke or TIA, 4617 [43.2%]). Among the overall cohort, 4591 (24.9%) patients achieved an LDL-C <1.8 mmol/L during 12 months of follow-up (MI, 1288 [35.4%]; PCI, 1542 [37.6%]; stroke or TIA, 1761 [16.5%]). Improvements in achieved LDL-C were observed over time with a mean LDL-C 2.64 (0.92) mmol/L and 20.0% of patients achieving an LDL-C <1.8 mmol/L in 2003 as compared with a mean LDL-C 1.86 (0.70) mmol/L and 53.9% of patients achieving an LDL-C <1.8 mmol/L in 2016. Conclusions: In this single centre cohort study from Hong Kong, nearly half of patients with MI, PCI, or stroke in 2016 appear to qualify for intensification of lipid-modifying drug treatment in order to achieve a treatment goal of LDL-C <1.8 mmol/L. Further research is required in Hong Kong to assess contemporary management of LDL-C in a larger group of patients with established atherosclerotic cardiovascular disease.